Predictive Factors of Death Anxiety in Caregivers of Hemodialysis Patients - Fatemeh Lashgari; Jalil Azimian; Mehdi Ranjbaran; Mohammad Ali Soleimani (Hamadan University of Medical Sciences, 2019)
Introduction: Due to the chronic and progressive nature of chronic renal failure, the hemodialysis patients' need for caregivers to carry out daily care increases; as a result of this care, caregivers are also exposed to a wide range of psychological and physical problems. One of the psychological symptoms experienced by caregivers is death anxiety. This study was conducted to determine the predictors of death anxiety in caregivers of hemodialysis patients. Methods: In this cross-sectional descriptive study (May to Jun 2018), 176 caregivers of hemodialysis patients were selected using convenience sampling method from hemodialysis centers of Qazvin. A demographic characteristics questionnaire and Templer Death Anxiety Scale (TDAS) were used to collect data. Data analysis was performed using descriptive and inferential statistics including multiple linear regression in SPSS 23. Results: The mean score of caregivers' death anxiety was 48.37±9.18. Multiple regression results showed that gender (b=4.163, P<0/05), caregiver's relation with patient and simultaneous responsibility for caring other patients were significant predictors of death anxiety. The coefficient of determination indicated that the independent variables of the regression model explain 20.7% of the changes in death anxiety. Conclusion: Considering the important role of caregivers of hemodialysis patients, paying attention to psychological complications of this population such as death anxiety and its effective factors are important. Based on these variables, support and educational programs can be conducted to control the death anxiety in caregivers.